Blast disease in ryegrass is similar to rice blast in regard to infection cell biology - Solorzano, Chantal; Dalby, Melinda; Valent, Barbara (My University, 2019)
Magnaporthe oryzae has been devastating to various grasses. This is especially true in food crops around the globe. Resistance has been implemented but has not been completely successful due to the variability of the fungus. It is hypothesized that this is due in part to the presence of disposable mini-chromosomes. Ryegrass blast pathogen is closely related to the dangerous, emerging wheat blast pathogen, and understanding it can help us understand wheat blast as well as pathogen variability. The ryegrass pathogen on its own recently emerged as a serious threat to golf courses and sports fields in the U.S. Hypothesis: The ryegrass pathogen uses the same biotrophic (live-cell) invasion strategy as the extensively-studied rice blast pathogen.
Keywords: USDA NIFA 2019-67032-29071